2015
DOI: 10.1371/journal.pone.0138315
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Analysis of Gonococcal and Chlamydial Infections among Men-Who-Have-Sex-with-Men in Cape Town, South Africa

Abstract: BackgroundMen-who-have-sex-with-men (MSM) are at high risk of HIV and sexually transmitted infection (STI) transmission. Asymptomatic STIs are common in MSM and remain undiagnosed and untreated where syndromic management is advocated. Untreated STIs could be contributing to high HIV rates. This study investigated symptomatic (SSTI) and asymptomatic STIs (ASTIs) in MSM in Cape Town.MethodsMSM, 18 years and above, were enrolled into this study. Participants underwent clinical and microbiological screening for ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 23 publications
(26 reference statements)
2
60
2
Order By: Relevance
“…17,19,39,5557 The proportions of men reporting sex under the influence of alcohol varied from 47.3% (Cape Town, South Africa) to 77.5% (Nairobi, Kenya). 17 Park et al 56 reported that 66.1% of the men had sexual intercourse after drinking alcohol in past 12 months (Cameroon); Rispel et al 19 reported that almost three-quarters (73.4%) of participants reported having sex while under the influence of alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…17,19,39,5557 The proportions of men reporting sex under the influence of alcohol varied from 47.3% (Cape Town, South Africa) to 77.5% (Nairobi, Kenya). 17 Park et al 56 reported that 66.1% of the men had sexual intercourse after drinking alcohol in past 12 months (Cameroon); Rispel et al 19 reported that almost three-quarters (73.4%) of participants reported having sex while under the influence of alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…42 Use of other specific drugs was less frequently reported; Lane et al 23 reported on use of ecstasy (4.0%); GHB (Gamma Hydroxybutyrate; 0.3%); methamphetamine: (“tik”; 0.3%), methaqualone (“mandrax”; 1.9%), methcathinone (“cat”; 0.3%), and nyaupe (cannabis and heroin; 1.3%), suggesting that use of such drugs is rare. However, Rebe et al 55 reported that 37% of MSM patients at a health clinic in Cape Town reported ever having used crystal methamphetamine; use was much lower among Black MSM compared to White and Coloured/other MSM (19%, 32%, and 57%, respectively). Use of specific drugs varied within countries; Nalá et al 49 reported prevalence of cannabis use in the preceding 12 months among MSM in Mozambique ranging from 4.0% (Nampula/Nacala) to 11.8% (Maputo).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the prior cross-sectional studies, individual-level factors such as multiple sex partners, engaging in transactional sex, inconsistent condom use, and alcohol use were associated with prevalent, 10, 11 . Risk for STIs cannot be attributed to a single factor, but rather a combination of factors that may include risks associated with specific characteristics of an individual’s sexual partnerships.…”
Section: Introductionmentioning
confidence: 97%